A model of human capital, time discounting and economic growth - Michal Bauer; Julie Chytilová (Charles University in Prague, Institute of Economic Studies (IES), 2008)
Endogenous time discounting is introduced in a two-period human-capital-driven growth model: subjective discount rate depends upon the level of human capital. This assumption accords strongly with the micro-level evidence. In the model an individual optimizes consumption over two periods. Low human capital societies do not grow fast since high discount rate discourages schooling as the major form of savings. This implication is further reinforced by modeling the efficiency of schooling in the context of population pressure which is also driven by low human capital. The model may produce multiple development regimes and it illustrates wider role of education in tackling possible development traps.
Keywords: D9; I2; O1; 330; growth; human capital; education; time discounting; discount rate; poverty; Humankapital; Bildung; Wirtschaftswachstum; Zeitpräferenz; Overlapping Generations; Theorie